Three-Column Osteotomy in Adult Spinal Deformity: An Analysis of Temporal Trends in Usage and Outcomes. (2nd November 2022) - Passias, Peter G.; Krol, Oscar; Passfall, Lara; Lafage, Virginie; Lafage, Renaud; Smith, Justin S.; Line, Breton; Vira, Shaleen; Daniels, Alan H.; Diebo, Bassel; Schoenfeld, Andrew J.; Gum, Jeffrey; et al.
Abstract : Background: Three-column osteotomies (3COs), usually in the form of pedicle subtraction or vertebral column resection, have become common in adult spinal deformity surgery. Although a powerful tool for deformity correction, 3COs can increase the risks of perioperative morbidity. Methods: Operative patients with adult spinal deformity (Cobb angle of >20°, sagittal vertical axis [SVA] of >5 cm, pelvic tilt of >25°, and/or thoracic kyphosis of >60°) with available baseline and 2-year radiographic and health-related quality-of-life (HRQoL) data were included. Patients were stratified into 2 groups by surgical year: Group I (2008 to 2013) and Group II (2014 to 2018). Patients with 3COs were then isolated for outcomes analysis. Severe sagittal deformity was defined by an SVA of >9.5 cm. Best clinical outcome (BCO) was defined as an Oswestry Disability Index (ODI) of <15 and Scoliosis Research Society (SRS)-22 of >4.5. Multivariable regression analyses were used to assess differences in surgical, radiographic, and clinical parameters. Results: Seven hundred and fifty-two patients with adult spinal deformity met the inclusion criteria, and 138 patients underwent a 3CO. Controlling for baseline SVA, PI-LL (pelvic incidence minus lumbar lordosis), revision status, age, and Charlson Comorbidity Index (CCI), Group II was less likely than Group I to have a 3CO (21% versus 31%; odds ratio [OR] = 0.6; 95% confidence interval [CI] = 0.4 to 0.97) and more likely to have an anterior lumbar interbody fusion (ALIF; OR = 1.6; 95% CI = 1.3 to 2.3) and a lateral lumbar interbody fusion (LLIF; OR = 3.8; 95% CI = 2.3 to 6.2). Adjusted analyses showed that Group II had a higher likelihood of supplemental rod usage (OR = 21.8; 95% CI = 7.8 to 61) and a lower likelihood of proximal junctional failure (PJF; OR = 0.23; 95% CI = 0.07 to 0.76) and overall hardware complications by 2 years (OR = 0.28; 95% CI = 0.1 to 0.8). In an adjusted analysis, Group II had a higher likelihood of titanium rod usage (OR = 2.7; 95% CI = 1.03 to 7.2). Group II had a lower 2-year ODI and higher scores on Short Form (SF)-36 components and SRS-22 total (p < 0.05 for all). Controlling for baseline ODI, Group II was more likely to reach the BCO for the ODI (OR = 2.8; 95% CI = 1.2 to 6.4) and the SRS-22 total score (OR = 4.6; 95% CI = 1.3 to 16). Conclusions: Over a 10-year period, the rates of 3CO usage declined, including in cases of severe deformity, with an increase in the usage of PJF prophylaxis. A better understanding of the utility of 3CO, along with a greater implementation of preventive measures, has led to a decrease in complications and PJF and a significant improvement in patient-reported outcome measures. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.